Investigation of R290 Flow Boiling Heat Transfer and Exergy Loss in a Double-Concentric Pipe Based on CFD - Jinfeng Wang (MDPI AG, 2021)
In this paper, the impact of different factors on the flow boiling of R290 and R22 in double-concentric pipes are investigated through CFD numerical simulations. The numerical studies are performed by changing the inner tube diameter in the range of 3 to 7 mm, the refrigerant velocity between 1 and 5 m/s, the water velocity between 1 and 10 m/s and the saturation temperature in the range of 276 to 283 K. The heat transfer coefficient (HTC), pressure drop and exergy destruction of R290 are determined. The results show that HTC, pressure drop and exergy destruction are significantly impacted by the pipe diameter and the refrigerant velocity, but slightly impacted by water velocity and saturation temperature. Moreover, the exergy loss and pressure drop of R290 are 11.8–13.3% and 4.3–10.2% lower than those of R22. R290 has a lower energy loss than R22 in the evaporation process in the double-concentric pipe. However, the HTC of R290 is 57.3–59.7% lower than that of R22. The HTC of R290 can be optimized by increasing the pipe diameter or the R290 velocity.